SOME ORGANIC CONSTITUENTS OF SCALES OF THE FISH CHANNA PUNCTATUS AT DIFFERENT STAGES OF GROWTH - Saraswat, R C (Indian Journal of Fisheries, 2011)
Changes with age in the aminoacid composition of arterial elastin havebeen studied by Lansing et al (1951) and the component amino acids of theprotein of fish Labeo rohita at different stages of growth have been reportedby Tiwari and Srivastava (1962). Ether extract (crude fat), nitrogen (crudeprotein) and aminoacid contents of the fins of the common cat fish Wallagoattu have been quantitatively studied by Saraswat and Ram (1972) at differentstages of growth.